An Empirical Analysis for Mode Choice in a Short-Distance Trip with Personal Rapid Transit - Hyunmyung Kim; Haneum Seok; Soyoung Iris You; Changju Lee (Journal of Advanced Transportation)
Recently, there have been emerging demands for new transportation modes, such as personal rapid transit (PRT), to improve the connectivity of first and last mile travel. Advancement of ICT and growing concerns over environmental issues reinforce such demands through which specific transportation modes can satisfy the need of each individual for short-distance trips. Although PRT has received particular attention for short-distance trips, it is true that recent approaches have been developed to analyze the behavior of travelers for mid- to long-distance trips that are not relevant for short-distance trips. This study proposed a suitable approach using logistic regression models that could assist the understanding of features which determine mode choice in a short-distance trip. The mode choice for PRT in short-distance trips in this study was based on the data from the survey. After considering various factors, it was apparent that the purpose of the trip together with weather conditions impacted significantly on travelers’ mode choices to PRT in short-distance trips. Additionally, it is expected that this study will play an important initial role in analyzing emerging transportation modes that can more easily respond to new demands for short-distance trips.